2008
DOI: 10.1136/sti.2007.026195
|View full text |Cite
|
Sign up to set email alerts
|

Measuring access: how accurate are patient-reported waiting times?

Abstract: The overall accuracy of patient reported waiting times was poor. Although nearly one in six patients misclassified themselves as being seen within or outside of 48 hours, given the under and overreporting rates observed, the overall impact on Health Protection Agency waiting time data is likely to be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Fifthly, the HPA GUM waiting time audits only sampled respondents for a 1-week period of time, and an earlier study reported that the accuracy of patient-reported waiting times was overall only 52% 12. The weak correlation with the number of new patients and sexual health screens performed may reflect both the quality of these data and the small number of audits taken over this 4-year period.…”
Section: Discussionmentioning
confidence: 97%
“…Fifthly, the HPA GUM waiting time audits only sampled respondents for a 1-week period of time, and an earlier study reported that the accuracy of patient-reported waiting times was overall only 52% 12. The weak correlation with the number of new patients and sexual health screens performed may reflect both the quality of these data and the small number of audits taken over this 4-year period.…”
Section: Discussionmentioning
confidence: 97%